Perencanaan Arsitektur Enterprise Sistem Informasi Pada STIE Dharma Iswara Madiun - Noordin Asnawi; M. Suyanto; Andi Sunyoto (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
Information system development process is not yet organized and well documented allowing implementation of information systems that are not aligned with the business needs of an organization. Enterprise Architecture Planning (EAP) is a methodology that can be used to plan the enterprise architecture that focus on data architecture, application architecture and technology architecture, and the planned implementation of the architecture enterprise that has been made. The purpose of planning is to create a blueprint of information system that includes data architecture, application architecture, technology architecture and implementation scheduling. The results of this planning is the establishment of a data entity, the proposed application, network architecture mapping and scheduling implementation as references in the development of information systems. Keywords—enterprise architecture, EAP, information system